THE ASSOCIATION BETWEEN OBESITY AND HYPERTENSION AMONG ELDERLY RESIDING IN A NURSING HOME: IS GENDER IMPORTANT? - Farapti, Farapti; Fadilla, Chusnul; Notobroto, Hari Basuki; Abdul Aziz, Saidatul Afzan (The Indonesian Journal of Public Health, 2025)
Introduction: Elderly exhibit an increased for health complications, including obesity and hypertension (HT).. Obesity has been demonstrated to increase the risk of HT and the mechanism is also often influenced by gender. Aims: The study aimed to analyze the association between obesity and hypertension among elderly in nursing home stratified by gender. Methods: A cross-sectional study was conducted on a sample of 54 elderly subjects in nursing home. A sphygmomanometer was used to assess blood pressure (BIA) and a Bioelectrical Impedance Analysis (BIA) to determine nutritional status includingbody mass index (BMI), body fat (BF), visceral fat (VF), and subcutaneous fat (SF). Analysis of data was performed using an independent t-test and Pearson correlation test. Results: Mean age of respondents was 71.28 ± 8.21, dominated by women (75.9%), and 27.8% had hypertension. Dietary intake indicate excess sodium intake, while potassium, calcium, magnesium, vitamin D, vegetables, and fruits intake remain low. All indicators of nutritional status assessment differ significantly by gender except BMI. However, the present study found that BMI is the only variable associated with systolic BP (p=0.023). Stratified by gender, it was found that BW, BMI, and VF in women were related to systolic BP (p=0.022; p=0.015; p=0.040; respectively), and no such relationship was observed in men. Conclusion: It is proven that obesity and hypertension were more prevalent among elderly women. It is imperative to check nutritional statusfor preventive action for other diseases, including hypertension.